Rain fade dynamics analysis for terrestrial microwave links operating in Malaysia - Zyoud, Alhareth M. T. (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
Rain fade refers to the absorption and scattering of a microwave signal by rain drops, which becomes a critical issue at frequencies above 10 GHz. Knowledge of the dynamics characteristics of rain fade is important for communication system designs since it determines the system availability and assigns the system resource. It is also very essential information for implementation of fade mitigation techniques. Limited research has been conducted on rain fade dynamics modeling and prediction. Those researches were conducted on rain fade dynamics data collected from the temperate regions not the tropical areas, where the rain intensity is very high. Prediction models which are available in literature and adopted by International Telecommunication Union – Radio (ITU-R) have been proposed for earth to satellite links only and not for terrestrial links. In this study 16 months measured rain attenuation data in Malaysia for six microwave links at four different frequencies (15, 23, 26 and 38 GHz) were analyzed. Two features of rain fade dynamics for terrestrial links were investigated: fade slope and fade duration, and compared to models proposed by ITU-R for those parameters. Significant discrepancies have been observed with prediction models and measured data. In the case of fade slope, ITU-R model did not fit the measured data for attenuation level higher than 4 dB. The number of events for measured data was higher than that predicted by ITU-R fade duration model, especially for short duration and for all attenuation levels. None of six link's measured fade slope and fade duration data fit with ITU-R prediction models. A new modified model for rain fade slope prediction has been proposed based on measured data. The proposed modified fade slope model fits the measured data at all four frequencies and for all attenuation levels.